Apakah Determinan dari Pengungkapan Laporan Keuangan Kawasan Strategis Nasional Gerbangkertasusila Via Internet? - Javelin Auffadiina; Dwi Suhartini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this research is as an effort to inspect the relationship between Disclosure of Local Government Financial Statements Via the Internet which is a dependent variable with independent variables, namely Regional Expenditure, Regional Wealth and Regional Prosperity using quantitative research methods. This research used secondary data with a total sample of 36 financial reports from six national strategic areas for six periods. Based on the results of testing the relationship between these variables, it was found that regional wealth has an influence on the disclosure of regional financial statements, while regional expenditure and original income do not have a direct impact on the disclosure of regional financial statements. In this study, it was also found that the completeness and ease of accessing financial statements in the Gerbangkertosusilo area was still inadequate and maximal. Keywords: Disclosure of Financial Statements via the Internet, Regional Expenditure, Regional Wealth and Regional Prosperity, Gerbangkertosusila